Effects of Transgenerational Plasticity on Morphological and Physiological Properties of Stoloniferous Herb Centella asiatica Subjected to High/Low Light - Li, Kenian; Chen, Jinsong; Wei, Qing; Li, Qian; Lei, Ningfei (Frontiers in Plant Science, 2018)
Environmentally induced transgenerational plasticity can increase success of progeny and thereby be adaptive if progeny experiences the similarly parental environment. The ecological and evolutionary significance of transgenerational plasticity in plant has been studied mainly in the context of sexual generations.. A pot experiment using the stoloniferous herb Centella asiatica was conducted to investigate the effects of high/low light treatment experienced by parental ramets (F0 generation) on morphological and physiological properties of offspring ramets (F2 generation) as well as growth performance. Light environment experienced by parental ramets (F0 generation) significantly influenced petiole length, specific petiole length, internode length of stolon, leaf area, specific leaf area (SLA), leaf nitrogen and chlorophyll contents, potential maximum net photosynthetic rate (Pmax) in offspring ramets subjected to parental or non-parental environments even after they were detached from the parental ramets. Potential maximum net photosynthetic rate (Pmax) of offspring ramets (F2 generation) from parental ramets (F0 generation) subjected to low light treatment was significantly greater than that of offspring ramets (F2 generation) from parental ramets (F0 generation) subjected to high light treatment. Potential maximum net photosynthetic rate (Pmax) of offspring ramets (F2 generation) subjected to parental light environment was greater than that of offspring ramets (F2 generation) subjected to non-parental light environment. The greatest biomass accumulation and total stolon length were observed in offspring ramets (F2 generation) subjected to low light treatment as parental ramets (F0 generation) experienced. When parental ramets (F0 generation) were subjected to low light treatment, biomass accumulation and total stolon length of offspring ramets (F2 generation) experiencing parental light environment were significantly greater than those of offspring ramets (F2 generation) experiencing non-parental light environment. Opposite pattern was observed in offspring ramets from parental ramets subjected to high light treatment. Our work provides evidence that transgenerational plasticity through both morphological and physiological flexibility was triggered across vegetative generations for stoloniferous herb C. asiatica subjected to high/low light treatment. The transgenerational plasticity can allow offspring ramets to present adaptive phenotype early without lag time in response to the current environment. Thus, it is very important for clonal plants in adapting temporally and spatially heterogeneous habitats.